2022
DOI: 10.1002/ps.6787
|View full text |Cite
|
Sign up to set email alerts
|

Fear effects on bank voles (Rodentia: Arvicolinae): testing for repellent candidates from predator volatiles

Abstract: BACKGROUND Arvicolinae rodents are known pests causing damage to both agricultural and forest crops. Today, rodenticides for rodent control are widely discouraged owing to their negative effects on the environment. Rodents are the main prey for several predators, and their complex olfactory system allows them to identify risks of predation. Therefore, the potential use of predators' scents as repellents has gained interest as an ecologically based rodent control method. In a two‐choice experiment, we investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 72 publications
(160 reference statements)
0
4
0
Order By: Relevance
“…Further investigations into their combined effects on prey are thus warranted. In addition, recent reports show that chemical cues from predators can be used for insect 51 and rodent 52 pest management. These studies have laid new foundations for future research on novel pest control materials and methods for spider mite and other plant pests.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further investigations into their combined effects on prey are thus warranted. In addition, recent reports show that chemical cues from predators can be used for insect 51 and rodent 52 pest management. These studies have laid new foundations for future research on novel pest control materials and methods for spider mite and other plant pests.…”
Section: Discussionmentioning
confidence: 99%
“…However, nonconsumptive effects of predators on prey fitness and forage may also contribute to pest biological control but have been rarely evaluated. 49 , 50 Two recent reports shed some light on this matter using insect 51 and mammal 52 predator–prey systems, respectively. The former indicated that predator cues can significantly reduce pest fitness and suppress pest population, and the latter shows that these cues can repel the pest.…”
Section: Introductionmentioning
confidence: 99%
“…An alternative strategy is integrating entomopathogens with semiochemicals and other natural enemies of insect pests that successfully manage insects (Sharma et al, 2019). A similar concept was recently used to protect agricultural and forest crops from the Arvicolinae rodents in Sweden (Villalobos et al, 2022). Although the application of entomopathogens or their products serves as a promising alternative to chemical pesticides, more research is still needed in this field to delve into their services thoroughly.…”
Section: Entomopathogenic Control Of Coleopteran Beetlesmentioning
confidence: 99%
“…New works on innovative rodenticide formulations associated with gels (that are often called rodenticide "soft baits"), liquids, polymers, and encapsulated active compounds point the way towards further development to effectively manage rodent populations and mitigate the negative effects of rodenticides [25][26][27]. Gels and liquids can be used not only for direct rodent control but also as a suitable matrix for the formulation of repellents [28] and antifeedants or as attractants for rodent monitoring using nontoxic baits. Non-toxic soft baits are increasingly used to monitor rodent abundance in commensal settings [29] and may be an effective attractant in agricultural fields as well.…”
Section: Rodent Control and Monitoringmentioning
confidence: 99%